Predictive models for thermal inactivation of human norovirus and surrogates in strawberry puree. (February 2019) - Bartsch, Christina; Plaza-Rodriguez, Carolina; Trojnar, Eva; Filter, Matthias; Johne, Reimar
Abstract: Frozen berries contaminated with human norovirus (hNV) have been frequently identified as cause of foodborne gastroenteritis. To prevent virus transmission, heating can be applied to the berries. Here, the thermal inactivation of hNV in strawberry puree was assessed. Due to the lack of a reliable system for hNV infectivity assessment, capsid integrity assays using RNase treatment prior to detection of protected viral RNA were applied. In addition, murine norovirus (MNV) and Tulane virus (TV) served as surrogates. The method was optimized to allow direct comparisons between the viruses. The results indicated that infectious MNV is slightly more stable than TV. Both viruses were completely inactivated (>7 log10 reductions) after treatment at 80 °C for 8 s. TV infectivity decreased faster than capsid-protected RNA. In addition, TV showed a markedly lower stability compared to hNV using capsid integrity assays. Predictive models were generated for all viruses and D - and ɀ-values were calculated. The tertiary model covering reduction of hNV capsid-protected RNA between 50 and 80 °C suggests that temperatures under 70 °C are not reliable for inactivation. About 3.5 log10 reductions are achieved by heating at 80 °C for 8 s. Further studies should focus on the model validation with direct hNV infectivity data. Highlights: Optimization of a method for testing heat inactivation of viruses in berry puree. Comparison of heat inactivation of human norovirus and surrogates in strawberry puree. >7 log-reduction of Tulane virus and murine norovirus at 80 °C for 8 s. 3.5 log-reduction of capsid-protected RNA of human norovirus at 80 °C for 8 s. Generation of predictive models for inactivation of human norovirus and surrogates.